Degradation of oxytetracycline by persulfate activation using a magnetic separable iron oxide catalyst derived from hand-warmer waste - Lee, Youn Jun; Lee, Chang Gu; Park, Seong Jik; Jho, Eun Hea (Applied Sciences (Switzerland), 2021)
Oxytetracycline (OTC) is a tetracycline antibiotic that is widely used in the drug therapy and livestock industry and may threaten human health and ecosystems when released into the environment. In this study, a catalyst was prepared from hand-warmer waste using a simple magnetic separation method. The prepared hand-warmer waste catalyst (HWWC) was used as a persulfate (PS) activator for OTC removal. Characterization methods, such as X-ray diffraction and scanning electron microscopy–energy dispersive X-ray spectrometry, were used to investigate the crystal structure, surface morphology, and weight ratios of the elements in the HWWC. The degradation efficiency of OTC in the presence of the catalyst and PS was studied, and the radical generation mechanism of the catalyst was investigated. The removal ratio of OTC by PS activation was greater than 99% for a reaction time of 24 min at a pH of 6. The effects of the HWWC dosage, PS concentration, and solution pH on OTC degradation were also investigated. The reuse test revealed that HWWC can be reused for eight cycles with great stability. These results suggest that PS activation using hand-warmer waste can be an efficient strategy for the degradation of antibiotics.
Keywords: Antibiotics; Fenton-like reaction; Hand-warmer waste; Magnetic separable iron oxide catalyst; Persulfate activation